The Biography and Contributions of Professor ‘Aun al-Sharif Qasim al-Sudani - Muhammad, Abdul Munim Ahmed (Journal of Islamic and Religious Studies, 2017)
This research work emphasizes on the biography, publications and contributions of the Sudanese prominent scholar ‘Aun al-Sharif Qasim who born in the North of Al-Khartoum, the capital of the republic of Sudan in 1933 A.D.He wrote many books in Arabic language and his famous book “A Dictionary of Colloquial Dialect in Sudan” specially deals with the studies on the Sudanese Colloquial Arabic language and its impact on the literary Arabic language. Likewise he wrote in literature and language and enriched his scholastic life with many publications. This research work tries to convey the most important book and to give a short thought on it.